Topical ozone therapy in the treatment of pharmacodermia in a dog (canis lupus familiaris) - de Siqueira Silva Júnior, José Ivaldo [UNESP]; dos Santos, Caio Simon Florêncio; Da Silva, Bruna Martins [UNESP]; dos Santos, Ivan Felismino Charas [UNESP]; Ferro, Barbara Sardela [UNESP]; Barros, Talyta Isly Silva; Tomacheuski, Rubia Mitalli [UNESP]; Simões-Mattos, Lucilene (Universidade Federal do Rio Grande do Sul, 2019)
Background: Pharmacodermia is a drug reaction that manifests itself on the skin and mucous membranes. The main drugs that cause pharmacodermia are β-lactam antibiotics. It has a rare occurrence in dogs and may present different clinical signs. Ozone therapy is used to treat various conditions, such as infections and inflammatory diseases. This therapy acts through oxidative stress generating a positive inflammatory response to the body and stimulating the formation of granulation tissue and angiogenesis. Since pharmacodermia is rare in dogs and reports of ozonized sunflower oil and ozone for treat pharmacodermia is are rare in the literature, this paper aimed to report the use of ozonized sunflower oil in the treatment of pharmacodermia in a young female Rottweiler dog assisted and treated at a private veterinary clinic in Garanhuns, Pernambuco, Brazil. Case: A 2-year-old Rottweiler female, weighting 53.3 kg was attended at a private veterinary clinic in Garanhuns (Pernambuco - PE) with a history of dystocia. The dog was submitted to ovary-hysterectomy under general anesthesia. After anesthesia recovery was prescribed omeprazol (1 mg/kg, orally (P.O) SID for 10 days), cephalexin (20 mg/kg, P.O. BID for 10 days), tramadol hydrochloride (4 mg/kg, P.O. BID for seven days), carprofen (4.4 mg/kg, P.O. SID for three days), and the use of Elizabethan collar. Furthermore, for topical treatment was described chlorhexidine digluconate (0.2%) and ointment of allantoin and zinc oxide, SID, for 10 days. Seven days after the surgical procedure, the owner's dog reported by a telephone call the appearance of wounds in the dorsal region of the dog. Ten days after surgery, the dog returned to the veterinary clinic for stitches removal and wounds evaluation. During the physical examination, observed the presence of two cutaneous wounds, one located in the cervicothoracic region and the other wound was identified in the thoracic region and presence of pain during palpation. The wounds presented purulent secretion, pink coloration, and presence of necrosis. No changes were observed in the physiological parameters during the physical examination. The owner reported normophagia, ingestion of water, normal defecation and urine. The wound region was clipped, and prescribed topical chlorhexidine digluconate (2%), allantoin with zinc oxide ointment every 8 hours, amoxicillin and clavulanate potassium (20 mg/kg, P.O. BID for 10 days), and dipyrone (20 mg/kg P.O. BID for five days). Five days after the beginning of the second treatment the owner reported no improvement and the increased of the lesion, although the dog presented normophagia, ingestion of water, normal defecation, and urine. Thus, according to a therapeutic history of the use of cephalexin and amoxicillin with clavulanate potassium, both belongings to the β-lactamic antibiotic, the clinical diagnosis of pharmacodermia was determined. Wound cleaning and debridement were performed It has been recommended to suspend the previous treatment, and prescribed the use of ozonized sunflower oil (4 drops in each wound, BID) until the complete healing, associated to cleaning with ozonized (47 μg/mL) saline solution (0.9%). The sunflower oil contained linoleic acid (48-74%) and oleic acid (14-39%), and it was purchased directly from the supplier. Discussion: Thirty days after the treatment with ozonized sunflower oil, there was complete remission of the wounds Five months after the treatment the dog returned to clinical examination. No remnants of the wounds were observed and there were no changes in the physiological parameters or in the laboratory exams. According to the present report case, the use of ozone therapy using the ozonized sunflower oil and saline solution (0.9%) is effective to treat wounds related to pharmacodermia.
Keywords: Ozonized sunflower oil; Skin; Small animals; Wound